THE IMPORTANCE OF CARDIAC REHABILITATION PHASE 1 AFTER PERCUTANEOUS TRANSLUMINAL CORONARY ANGIOPLASTY IN ACUTE MYOCARDIAL INFARCTION WITH STORM LEVEL SURFACES - Silva, Gleide Campos da (2020)
This study aimed to demonstrate the importance of phase 1 cardiac rehabilitation after percutaneous transluminal coronary angioplasty (PTCA) in ST-segment elevation acute myocardial infarction (AMI). The objective was to describe the importance of phase 1 cardiac rehabilitation after angioplasty, percutaneous transluminal coronary artery in ST-segment elevation acute myocardial infarction, as well as to analyze the factors that cause acute myocardial infarction and to investigate its main characteristics. The research was based on a literature review with the qualitative method, using electronic databases such as Scielo, Birene Lilacs and others. The study revealed that physical therapy has been of paramount importance in post-stage cardiac rehabilitation (PTCA) in acute ST myocardial infarction. The physiotherapeutic goal is to reestablish the early return to activities of daily living, and can be characterized as a set of fundamental actions to ensure patients with heart disease better physical, psychological and social conditions,  enabling them to perform their activities of daily living.